Incidence of Positive Human Papillomavirus High Risk in Negative Cytology Result: Insidensi Kejadian Human Papillomavirus RisikoTinggi Positif pada Hasil Sitologi Negatif - Junita Indarti; Darrell Fernando; Finish Fernando; Ribkhi A. Putri; Anggara Mahardika; Muhammad Ikhsan (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstract Objective: This research aim is to report the incidence of positive HPV high risk in negative cytology result. Method: We collected 83 women underwent liquid-based cytology (LBC) and HPV DNA examination at the same time. We were using DiagCor GenoFlow Human Papillomavirus Array Test (GenoFlow), a novel HPV test based on PCR and "Flow-through" hybridization that can identify 33 HPV subtypes: 18 types of High risk HPV such as 16, 18, 31, 33, 35, 39, 45, 51, 52, 53, 56, 58, 59, 66, 68, 73, 81 and 82 Result: We grouped the subjects based on age below or equal to 30 years old (n=6) and above 30 years old (n=77). We found a significant difference in HPV DNA result within this group (P = 0.034), with 19.3% had HPV DNA type 16 and 18 in a group of age above 30 years old. Our study showed that 27 women (32.5%) underwent screening for cervical cancer having negative LBC result but showed positive HPV DNA positive. Conclusion: We found a significant difference in HPV DNA test result among women above 30 years old. Co-testing of Pap and HPV DNA is needed, especially if HPV DNA type 16 and 18 were found among negative Pap results. Keywords: Cervical cancer, HPV DNA, incidence, LBC, screening Abstrak Tujuan: Penelitian ini bertujuan melaporkan insidensi dari HPV risiko tinggi yang positif pada hasil sitologi negatif. Metode: Kami mengumpulkan 83 wanita yang menjalani liquid based cytology (LBV) dan pemeriksaan HPV DNA pada waktu yang bersamaan. Dengan menggunakan DiagCor GenoFlow Human Papilloma Virus Array Test (GenoFlow), yaitu sebuah uji HPV terbaru yang berbasis PCR dan â€œFlow-througâ€ hybridization dapat mengidentifikasi 33 subtipe HPV: 18 tipe HPV risiko tinggi seperti 16, 18, 31, 33, 35, 39, 45, 51, 52, 53, 56, 58, 59, 66, 68, 73, 81 dan 82. Hasil: Kami mengelompokkan subjek berdasarkan usia dibawah atau setara 30 tahun dan diatas 30 tahun (n=77). Kami menemukan perbedaansignifikan dari hasil HPV DNA dalam kelompok ini (P=0.034), dengan 19.3% memiliki HPV DNA tipe 16 dan 18 dalam kelompok usia diatas 30 tahun. Penelitian ini menunjukkan 27 perempuan (32.5%) menjalani skrining kanker serviks memiliki hasil LBC yang negatif namun menunjukkan HPV DNA positif. Kesimpulan: Terdapat perbedaan signifikan dari uji HPV DNA pada wanita usia diatas 30 tahun. Pemeriksaan bersamaan antara Pap dan HPV DNA dibutuhkan terutama ketika HPV DNA tipe 16 dan 18 ditemuka pada hasil Pap negatif. Kata kunci: HPV DNA, insidensi, kanker serviks, LBC, skrining